Epicondylitis among cooks in nursery schools. Issue 3 (March 1998) - Ono, Y; Nakamura, R; Shimaoka, M; Hiruta, S; Hattori, Y; Ichihara, G; Kamijima, M; Takeuchi, Y
Abstract : OBJECTIVES: To investigate the prevalence and risk factors of epicondylitis among cooks in nursery schools in a cross sectional study because they are suspected to have strenuous workloads on the hands and arms. METHODS: Prevalence of epicondylitis among 209 nursery school cooks and 366 control workers aged 40-59 were studied. Both groups consisted of women workers chosen from 1299 subjects who agreed to participate from 1329 social welfare employees in a city. All workers were interviewed with a questionnaire and had a clinical examination of the tenderness to palpation of epicondyles and epicondylar pain provoked by resisted extension and flexion of the wrist. RESULTS: Nursery school cooks had a significantly higher prevalence of epicondylitis (11.5%) than the controls (2.5%). In a logistic regression model, job title of the cook was also found to have a strong association with epicondylitis (odds ratio (OR) 5.4, 95% confidence interval (95% CI) 2.4 to 11.9) after adjustment for age, body length, and body mass index. Weaker associations were also found between epicondylitis and suspected job stress or workload scores for mechanical workload and psychosocial stressors based on factor analysis. CONCLUSIONS: This study supported the hypothesis that nursery school cooks had a higher prevalence of epicondylitis than other workers with less strenuous hand and arm tasks. It was suggested that risk factors of epicondylitis would be multifactorial, including mechanical workload and psychosocial factors.